Production of a New Plant-Based Milk from Adenanthera pavonina Seed and Evaluation of Its Nutritional and Health Benefits - Afolabi, Israel Sunmola; Nwachukwu, Irene Chiamaka; Ezeoke, Chinemelum Sandra; Woke, Ruth Chineme; Adegbite, Olawunmi Adebisi; Olawole, Tolulope Dorcas; Martins, Olubukola C. (Frontiers in Nutrition, 2018)
A new plant milk was discovered from the seed of Adenanthera pavonina. The physicochemical and nutritional properties of the new pro-milk extract were assessed, and their biochemical effects were compared with those of soy bean extracts. Eleven groups of three albino rats each were used to assess the health benefits of the pro-milk. Groups were separately administered 3.1, 6.1 and 9.2 µl/g animal wt. pro-milk extract from A. pavonina seed; 6.1 µl/g animal wt. milk extract from soy-bean; and 6.1 µl/g animal wt. normal saline for 7 days or 14 days. The ‘baseline’ group consisted of those sacrificed on day 0. Among the physical properties considered, the pro-milk from A pavonina had significantly higher (P<0.05) hue colour value and significantly lower (P<0.05) L* than that from soy bean did. The pro-milk from A. pavonina had a significantly higher (P<0.05) levels of protein (36.14±0.12 %), Ca (440.99±0.93 mg/L), Mg (96.69±0.03 mg/L), K (190.41±0.11 mg/L), Na (64.24±0.24 mg/L) and Cu (0.55±0.24 mg/L), and a significantly lower (P<0.05) levels of Mn (0.04±0.01 mg/L) and vitamins A (undetectable), C (1.87±0.01 mg/100g), and E (0.12±0.01 mg/100g) compared to those of soy milk. The daily consumption of the pro-milk extract from A. pavonina for 14 days significantly reduced (P<0.05) Ca+-ATPase at low dose (3.1 µl/g animal wt.), but significantly increased (P<0.05) Mg2+-ATPase at high dose (9.2 µl/g animal wt.). Daily administration of the A. pavonina extract for 14 days caused a significant reduction (P<0.05) in acetylcholinesterase activity in the liver, intestine, heart and kidney, suggesting that the pro-milk may facilitate ions transportation across the membrane. The pro-milk offers promising beneficial effects for patients with neurological diseases, as well as supporting general health owing to the high protein and mineral content. Vitamins fortification is recommended during production.